Improving the Reading Skills of Grade 5 Struggling Readers Through the Use of Interactive Learning Resources - Sotelo, Rhea (SAFE-Network, 2024)
Notably, the use of technology in teaching and reading instruction was found to have various effects on learners' attitudes towards engagement with the text and meaning-making. As a result, online sources as authentic materials can be an ideal resource for reading instruction. Given the context in which instruction is carried out in the new normal and the kind of intervention needed for the different learner groups where their reading skills is concerned, learning resources in interactive formats are optimized for maximum results. Specifically, the use of interactive learning resources such as the digital learning objects has become a valuable for teachers with regards to reading instruction. Its use in the different phases of instruction proved to be a valuable tool in addressing the reading difficulties of the elementary learners. Using the content-validated test as research instruments, results of the study showed how the Grade 5 struggling readers of Baquioen Elementary School benefitted from the use of interactive learning resources in reading instruction during the school year 2021-2022. Moreover, the results of the study reveal that there was significant difference in the levels of reading skills of the Grade 5 struggling readers after they were taught in English using digital learning objects. Thus, teachers are recommended to scaffold the reading instruction with the use of tools that target the best ways in which the students learn best.